KEMAMPUAN SOSIAL GURU BAHASA ARAB MADRASAH ALIYAH NEGERI KOTA PALANGKARAYA - Nurul Aisyatul Ridha; Ahmadi; Marsiah; Nurul Wahdah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2023)
The role of a teacher in the learning process occupies a very important position in improving the abilities of students, for this requires skills and one of them is social skills. This research aims to understand the social skills of Arabic teachers at Madrasah Aliyah Negeri Palangka Raya City. This research uses a qualitative descriptive method with a phenomenological approach, which requires searching for information that can be interpreted correctly. Based on the results of data processing, it was concluded that Arabic language teachers at the State Madrasah Aliyah in Palangka Raya City were very adept at socializing. interact and communicate. to fellow teachers, madrasa heads, student parents, and the environment around the madrasa. From this explanation, it can be understood that the Arabic language teacher at Madrasah Aliyah Negeri Palangka Raya City has applied social skills in the learning process by being inclusive, impartial, and not discriminating against anyone such as gender, religion, race, or physical condition, background. family, and socio-economic status of students.